A web-based, patient-centered toolkit to engage patients and caregivers in the acute care setting: a preliminary evaluation. (2nd August 2015) - Dalal, Anuj K; Dykes, Patricia C; Collins, Sarah; Lehmann, Lisa Soleymani; Ohashi, Kumiko; Rozenblum, Ronen; Stade, Diana; McNally, Kelly; Morrison, Constance RC; Ravindran, Sucheta; Mlaver, Eli; Hanna, John; et al.
Abstract: We implemented a web-based, patient-centered toolkit that engages patients/caregivers in the hospital plan of care by facilitating education and patient-provider communication. Of the 585 eligible patients approached on medical intensive care and oncology units, 239 were enrolled (119 patients, 120 caregivers). The most common reason for not approaching the patient was our inability to identify a health care proxy when a patient was incapacitated. Significantly more caregivers were enrolled in medical intensive care units compared with oncology units (75% vs 32%; P < .01). Of the 239 patient/caregivers, 158 (66%) and 97 (41%) inputted a daily and overall goal, respectively. Use of educational content was highest for medications and test results and infrequent for problems. The most common clinical theme identified in 291 messages sent by 158 patients/caregivers was health concerns, needs, preferences, or questions (19%, 55 of 291). The average system usability scores and satisfaction ratings of a sample of surveyed enrollees were favorable. From analysis of feedback, we identified barriers to adoption and outlined strategies to promote use.